Developing Leadership and Management Competencies in Maritime Vocational Education: A Qualitative Study - Larsen Barasa; Tri Cahyadi; Imam Fahcruddin; Hendrawan Hendrawan; Faisal Aswin; Jay Singgih (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This research investigates the effectiveness of maritime vocational education in developing leadership and management competencies, focusing on ethical decision-making, global competence, and innovation. A qualitative approach was used to gather insights from 24 participants, including maritime professionals, lecturers, graduates, and senior government officers. The results reveal that maritime vocational schools are highly effective in fostering leadership skills, with an overall average score of 9/10 across various indicators. However, graduates indicated a need for more practical, hands-on learning experiences to better transition into professional leadership roles. The study suggests that further collaboration between maritime vocational schools and industry stakeholders is essential to ensure curriculum relevance and alignment with industry demands. By enhancing practical learning opportunities and addressing gaps in leadership training, maritime vocational education can continue to play a critical role in preparing future leaders for the complexities of the global maritime industry.